PENGARUH PUPUK KANDANG SAPI DAN PUPUK NPK MUTIARA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG UNGU (Solanum melongena L. ) - Hendri, Martinus; Napitupulu, Marisi; Sujalu, Akas Pinaringan (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
Effect of NPK Mutiara and Cow Manure Fertilizers on the Growth and Yield of  Eggplant         (Solanum melongena L.) Objective of the research was (1) to study the effect of NPK Mutiara and cow manure fertilizers, as well as their interaction on the growth and yield of purple eggplant; and (2) to find out the proper NPK Mutiara dan cow manure fertilizers dosage that affect high yield.The research was carried out in Melapeh Baru Village, Linggung Bigung Sub Disctrict of West Kutai District, East Kalimantan Province.  It lasted for four months (February 2013 to May 2013).The Randomised Completely Block Design was employed for this research with  factorial 4 x 4 and 3 replications.  The first factor was NPK Mutiara fertilizer (M), consisted of 4 levels: no NPK Mutiara application (m0), 20 gr per plant (m1), 40 gr per plant (m2) ,and 60gr per plant(m3).  And the second factor was cow manure fertilizer (P) consisted of 3 levels : no NPK Pelangi application (p0), 500 gr per plant(p1), 750gr per plant (p2) ,and1000 gr per plant (p3).Results of the research indicated that: The application of NPK Mutiara fertilizer affected significantly on plant height at 30 and 45 days after sowing, number of fruits per plant,  length of fruit, heavy fruit per crop, and weight per piece.  The highest  heavy fruit per crop was attained on 20 gr per plant NPK Mutiara application with 1587,78 gr per plant, meanwhile the lowest one was found on no NPK Mutiara application with only 825 gr per plant.The  application  of  cow manure fertilizer   affected  very    significantly on plant height at 15, 30, and 45 days after sowing, number of fruits per plant, length of fruit, heavy   fruit per crop,  and    weight  per piece.  The highest  production of  heavy fruit per crop was attained on 500 gr per plant cow manure  application with 1644 gr per plant,  meanwhile the lowest one was found on no cow manure application with only 425,16 gr per plant;  and The interaction effect between NPK  Mutiara   and cow  manure  fertilizers application was  significant on   number of fruits    per plant, length of fruit, heavy fruit  per  crop, and  weight  per  piece, and  not  significant  on plant  height  at 15 days after sowing, and fruit diameter.